Impacts of the COVID-19 Pandemic on Forest Resource Use by Rural Communities in India - Fischer, Harry; Schultz, William; Filippi, Anthony; Fleischman, Forrest; Gupta, Divya; Güneralp, Burak; Ramprasad, Vijay; Rana, Pushpendra; Rodriguez-Solorzano, Claudia; Singh, Devanshi (Swedish University of Agricultural Sciences, 2024)
Description:

This project, “Impacts of the COVID-19 Pandemic on Forest Resource Use by Rural Communities in India” aims to study the role of forest plantations as a safety net for rural households facing distress during the COVID-19 pandemic. The data was collected in 2021-22.

The data includes:

- Village information on demographics and resource governance
- Household information on demographics, livelihoods, impacts of the COVID-19 pandemic, and forest use and management
- Information on forest plantations, including species and management


Data structure:

This dataset contains 720 households nested within 24 local governmental units (panchayats) in the Kangra District of India’s northern state of Himachal Pradesh.

This data builds a panel dataset with previously collected data in 2018, “Impacts of Afforestation on Sustainable Rural Livelihoods in India”, which is publicly available here: https://conservancy.umn.edu/handle/11299/220402 .

The data from 2018 included 2400 households nested within 60 panchayats (40 households per panchayat). The current dataset has selected 24 panchayats from the previous study, and randomly selected 30 households from the original sample in each panchayat to resurvey in 2021-22.

The panel dataset thus enables comparison of forest use patterns before the pandemic (2018) with forest use during/after pandemic disruptions (2021-22) for 720 households.

At present, we post the raw, unprocessed data. We have removed all person names to protect identity of surveyed households. The documentation files include full information about variables collected.

I projektet “Impacts of the COVID-19 Pandemic on Forest Resource Use by Rural Communities in India” undersöks vilken roll skogsplantager har som skyddsnät för hushåll på landsbygden som drabbats av covid-19-pandemin. Uppgifterna samlades in 2021-22. Datasetet innehåller rådata från projektet. För utförligare beskrivning se den engelska versionen.
Effekter av Covid-19-pandemin på skogsresursanvändning i landsbygdssamhällen i Indien
Keywords: FOREST MANAGEMENT; SKOGSSKÖTSEL; RURAL DEVELOPMENT; LANDSBYGDSUTVECKLING; NATURAL RESOURCES; NATURRESURSER; community-based resource management; community-based resource management; natural resource governance; natural resource governance; forest livelihoods; forest livelihoods; forest restoration; forest restoration; tree planting; tree planting; human well-being; human well-being; COVID-19; COVID-19; forests safety net; forests safety net; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Natural landscapes; Naturlandskap; Forest Science; Skogsvetenskap; Human Geography; Kulturgeografi; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap